EFISIENSI PEMASARAN JAGUNG BISI-18 (Zea mays) di DESA KEANG KECAMATAN KALUKKU KABUPATEN MAMUJU - Amin, Nur Silfiah (AgriMu, 2022)
Corn is a plant that has many benefits so that corn has a strategic role in the Indonesian economy. Fluctuating price conditions cause uncertainty in the profits obtained by farmers or marketing institutions involved, so it is necessary to research corn marketing efficiencyThis research was conducted in Keang Village, Kalukku District, Mamuju Regency. To determine the sample, it was done by snowball sampling, namely by tracing the entire population that was sampled as many as 25 people who were involved in marketing corn. The analytical techniques used include cost and profit analysis, marketing margin analysis and marketing channel efficiency analysis.Corn marketing channel in Keang Village, Kec. Kalukku, Kab. Mamuju has 2 marketing channels. The highest marketing margin received by marketing institutions is Rp. 3,200,- while the lowest is Rp. 300,- and the highest profit is Rp. 6,266,- while the lowest profit obtained by marketing institutions is Rp. 3,218,-. Corn marketing channel in Keang Village, Kec. Kalukku, Kab. Mamuju is considered efficient, and the most efficient is 0.2%. Keywords: Corn, Marketing, Cost, Profit, Efficiency